The diversity benefits of marine artificial structures: A global meta-analysis with implications for offshore wind farms and nature-inclusive design - Katherine Richards; Pippa J. Moore (Ecological Engineering, 2026)

Assessing the co-location potential of seaweed aquaculture and offshore wind farms in UK waters using habitat suitability models - Ethan Clark; Pippa J. Moore; Rodney M. Forster; Harry Burton; Clare Fitzsimmons (Aquaculture, 2026)

Abundance-based distribution modelling reveals climate-driven loss of functionally important kelp forest habitat - Patrick Eskuche-Keith; Heather E. Sugden; Michael T. Burrows; Pippa J. Moore; Clare Fitzsimmons; Dan A. Smale; Benjamin Hall; Fabrice Stephenson (Journal of Environmental Management, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Determining the contribution of temperate seaweed farming to local sedimentary carbon stocks and climate change mitigation - Maxine C. Canvin; Nathan G. King; Pippa J. Moore; Dan A. Smale (Marine Pollution Bulletin, 2026)

Evaluating the effects of management regime on the recovery process of Lessonia trabeculata to harvesting - Catalina S. Ruz; Pippa J. Moore; Alejandro Pérez-Matus (Journal of Applied Phycology, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

The ecology of the oxyscape in coastal ecosystems - Marco Fusi; Fabrice Stephenson; Sergio A. Navarrete; Fabian J. Tapia; John L. Largier; Ramona Marasco; Theresa Rueger; Chancey MacDonald; Daniele Daffonchio; Miriam Fernandez; Evie A. Wieters; Jenny Booth; et al. (Trends in Ecology & Evolution, 2025)

Chemical composition of the harvested subtidal kelp, Lessonia trabeculata, from a coastal location in central Chile - Camila Gonzalez-Alonso-de-Linaje; Pippa Moore; Dan Smale; Louise Delion; Catalina S. Ruz; Rodrigo Muñoz-Cordovez; Praxedes Muñoz; Fadia Tala; Roberto A. Uribe; Alejandro Pérez-Matus (Algal Research, 2025)

Can the Emerging European Seaweed Industry Contribute to Climate Change Mitigation by Enhancing Carbon Sequestration? - Maxine C. Canvin; Ana R. Borrero‐Santiago; Tom Brook; Mollie Gupta; Jessica Knoop; Georgina Menage; Pippa J. Moore; Nessa E. O'Connor; Aurora M. Ricart; Dan A. Smale (Reviews in Aquaculture, 2025)
Blue carbon habitats, which exhibit high rates of natural carbon sequestration, typically refer to salt marshes, seagrass meadows, and mangrove forests. Recent studies, however, have argued for the inclusion of seaweed‐dominated habitats, like kelp forests, into blue carbon frameworks. Farmed seaweed may also function as a blue carbon habitat, with large‐scale seaweed aquaculture suggested as a climate change mitigation strategy, but the evidence base remains limited. Here, existing knowledge on the mechanisms influencing carbon uptake, release, transport, and storage from kelp farms was synthesised, and a literature review was conducted to quantify associated rates of carbon sequestration. We identified strong geographical and methodological biases in the literature, with the majority of studies conducted in Asia and focusing on primary production rates as a proxy for carbon sequestration potential. Estimates of carbon release and storage rates were highly variable across locations, species, and approaches, and a scarcity of research on dissolved organic carbon, sedimentary carbon, and net ecosystem productivity was identified. Although the European kelp farming industry is in its infancy, it is predicted to expand to meet increasing demand for seaweed biomass. This is incentivised by perceived associated ecosystem service benefits such as enhanced carbon sequestration. However, multiple factors including environmental concerns, a lack of quantitative evidence, operational challenges, and regulatory complexities hinder industry expansion. Based on both the synthesised empirical evidence and an examination of key barriers and knowledge gaps, we identify future challenges and research priorities needed to assess the role of seaweed farming for climate change mitigation.

Baseline matters: Challenges and implications of different marine heatwave baselines - Kathryn E. Smith; Alex Sen Gupta; Dillon Amaya; Jessica A. Benthuysen; Michael T. Burrows; Antonietta Capotondi; Karen Filbee-Dexter; Thomas L. Frölicher; Alistair J. Hobday; Neil J. Holbrook; Neil Malan; Pippa J. Moore; et al. (Progress in Oceanography, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Quantifying growth, erosion and dislodgement rates of farmed kelp (Saccharina latissima) to examine the carbon sequestration potential of temperate seaweed farming - Maxine C. Canvin; Pippa J. Moore; Dan A. Smale (Journal of Applied Phycology, 2024)
Seaweed cultivation, including kelp species, is rapidly expanding in many regions. A widely assumed co-benefit of seaweed farming is increased local carbon sequestration rates (thereby contributing to climate change mitigation), although direct field-based measurements of carbon assimilation and release are largely lacking. We quantified growth, erosion and dislodgement rates of farmed Saccharina latissima in Porthallow Bay (Cornwall, UK) throughout a typical cultivation season to provide insights into the carbon sequestration potential of small-scale kelp farms. Blade elongation rates increased from ~ 1.3 cm day −1 to ~ 2.3 cm day −1 in March–April, before declining to 1.4 cm day −1 by May. Meanwhile, erosion rates remained low, ranging from ~ 0.5 to ~ 0.8 cm day −1 . Dislodgement rates decreased from 20% of plants in January–February to 5% in April–May. Rates of carbon accumulation and loss increased from January to May, related to an increase in standing stock. Conservative first-order estimates suggest that the farm captures 0.14 t C ha −1 y −1 , of which up to 70% is released into the environment as particulate organic carbon. Based on previous estimates of carbon burial and storage rates, the farm may sequester 0.05 t CO 2 e ha −1 y −1 . These values suggest that scaling-up European kelp farming should be motivated by other co-benefits, such as low-carbon product alternatives, job creation and potential biodiversity gains, and not be solely driven by a perceived meaningful increase in carbon sequestration. Importantly, further information needs to be obtained from a variety of cultivation sites to develop a better understanding of carbon dynamics associated with kelp farms.

Temporal variation in the structure, abundance, and composition of Laminaria hyperborea forests and their associated understorey assemblages over an intense storm season - Hannah S. Earp; Dan A. Smale; Peter M. Almond; Harry J.N. Catherall; Adam Gouraguine; Catherine Wilding; Pippa J. Moore (Marine Environmental Research, 2024)

Spatial and temporal variation in the diversity and structure of understorey macrofaunal assemblages within Laminaria hyperborea forests in the northeast Atlantic - Hannah S. Earp; Dan A. Smale; Nathan G. King; Jacob Bestwick; Brandon Fazel; Pippa J. Moore (Journal of Experimental Marine Biology and Ecology, 2024)

Temporal and spatial drivers of the structure of macroinvertebrate assemblages associated with Laminaria hyperborea detritus in the northeast Atlantic - Adam Gouraguine; Dan A. Smale; Arwyn Edwards; Nathan G. King; Mathilde Jackson-Bué; Sean Kelly; Hannah S. Earp; Pippa J. Moore (Marine Environmental Research, 2024)

Upscaling marine forest restoration: challenges, solutions and recommendations from the Green Gravel Action Group - Georgina Valentine Wood; Karen Filbee-Dexter; Melinda Ann Coleman; Jurgen Valckenaere; J. David Aguirre; Paige M. Bentley; Paul Carnell; Phoebe Damayanthi Dawkins; Lauren N. Dykman; Hannah S. Earp; Leeann B. Ennis; Prue Francis; et al. (Frontiers in Marine Science, 2024)
Introduction To counteract the rapid loss of marine forests globally and meet international commitments of the UN Decade on Ecosystem Restoration and the Convention on Biological Diversity ‘30 by 30’ targets, there is an urgent need to enhance our capacity for macroalgal restoration. The Green Gravel Action Group (GGAG) is a global network of 67 members that are working on the restoration of a diverse range of macroalgal forests and it aims to facilitate knowledge exchange to fast-track innovation and implementation of outplanting approaches worldwide. Methods Here, we overview 25 projects conducted by members of the group that are focused on testing and developing techniques for macroalgal restoration. Based on these projects, we summarise the major challenges associated with scaling up the area of marine forests restored. Results We identify several critical challenges that currently impede more widespread rollout of effective large-scale macroalgal restoration worldwide: 1) funding and capacity limitations, 2) difficulties arising from conditions at restoration sites, 3) technical barriers, and 4) challenges at the restoration-policy interface. Discussion Despite these challenges, there has been substantial progress, with an increasing number of efforts, community engagement and momentum towards scaling up activities in recent years. Drawing on the collective expertise of the GGAG, we outline key recommendations for the scaling up of restoration efforts to match the goals of international commitments. These include the establishment of novel pathways to fund macroalgal restoration activities, building skills and capacity, harnessing emerging innovations in mobile hatchery and seeding technologies, and the development of the scientific and governance frameworks necessary to implement and monitor macroalgal restoration projects at scale.

Mechanistic simulations of kelp populations in a dynamic landscape of light, temperature, and winter storms - Tim M. Szewczyk; Pippa J. Moore; Dan A. Smale; Thomas Adams; Michael T. Burrows (Ecological Modelling, 2024)

Spatiotemporal variability in the structure and diversity of understory faunal assemblages associated with the kelp Eisenia cokeri (Laminariales) in Peru - Roberto A. Uribe; Dan A. Smale; Robinson Morales; Solange Aleman; Dennis Atoche-Suclupe; Michael T. Burrows; Hannah S. Earp; Juan Diego Hinostroza; Nathan G. King; Angel Perea; Alejandro Pérez-Matus; Kathryn Smith; et al. (Marine Biology, 2024)
Kelp species function as foundation organisms in coastal marine ecosystems, where they alter environmental conditions and promote local biodiversity by providing complex biogenic habitat for an array of associated organisms. The structure and functioning of kelp forest ecosystems in some regions, such as along the Peruvian coastline, remain critically understudied. We quantified the structure and diversity of faunal assemblages within both holdfast and understory reef habitats within Eisenia cokeri forests. We sampled both habitat types within four subtidal kelp forests on multiple occasions between 2016 and 2020, and quantified fauna at a fine taxonomic level (mostly species). We recorded a total of ~ 55,000 individuals representing 183 taxa across the study, with holdfast assemblages typically exhibiting higher richness, abundance and biomass values compared with understory reef-associated assemblages. Holdfast assemblages were structurally and functionally dissimilar to those on reef surfaces and were less variable and consistent across sites and sampling events. Even so, assemblages associated with both habitat types varied significantly between sites and sampling events, with variation in upwelling strength, ocean currents, and grazing pressure among potential drivers of this ecological variability. Overall, E. cokeri supports diverse and abundant holdfast assemblages and functions as a foundation organism in Peru. Given that no other habitat-forming kelp species persist at the low latitudes of E. cokeri in mid-to-north Peru, the lack of functional redundancy suggests that effective management and conservation of this species is vital for wider ecosystem processes and biodiversity maintenance.

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

The influence of environmental context on community composition in artificial rockpools associated with seawalls - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2024)

Population structure and reproductive states of the dogwhelk Nucella lapillus differ between artificial structures and natural rocky shores - Bryan Thompson; Paul R. Brooks; Veronica Farrugia Drakard; Fiona Kubin; Hannah S. Earp; Ignacio Alvarez-Cienfuegos; Pippa J. Moore; Tasman P. Crowe (Marine Environmental Research, 2023)

Spatial variability in the structure of fish assemblages associated with Laminaria hyperborea forests in the NE Atlantic - Mathilde Jackson-Bué; Dan A. Smale; Nathan G. King; Aaron G. Rushton; Pippa J. Moore (Journal of Experimental Marine Biology and Ecology, 2023)

Artificial rockpools: Seaweed colonisation and productivity vary between sites but are consistent across environmental contexts - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2023)

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

Examining the production, export, and immediate fate of kelp detritus on open‐coast subtidal reefs in the Northeast Atlantic - Dan A. Smale; Albert Pessarrodona; Nathan King; Pippa J. Moore (Limnology and Oceanography, 2022)
Kelp forests are highly productive coastal habitats and are emerging as important sources of organic matter for other ecosystems. Although their high rates of productivity and detritus release are expected to lead to substantial export of carbon, few studies have actually quantified rates of export or the persistence of detritus. We addressed this in eight subtidal kelp forests ( Laminaria hyperborea ) spanning the length (9° of latitude) of the United Kingdom. Specifically, we quantified detritus production, retention/export from source and adjacent habitats, and in situ decomposition rates. Detritus released via both dislodgment of whole plants and “May cast” shedding of old growth was highly variable between sites with greatest values recorded in our colder, northern sites. This was attributable to greater plant size biomass in northern regions, rather than plant density or dislodgement rates. On average, the annual production of kelp detritus was 4706 ± 700 g FW m −2 yr −1 or 301 g C m −2 yr −1 . Low retention of detritus within the kelp forest and adjacent sedimentary habitats indicated very high rates of export (> 98% across the study). A litterbag experiment showed detritus may take > 4 months to decompose, suggesting great potential for long distance transport. Overall, our findings suggest that L. hyperborea forests export large amounts of detritus subsidies across their range, which can potentially shape the structure of distant benthic communities and constitute a relevant and largely overlooked flux in the coastal carbon cycle, which may represent an important component of natural carbon sequestration.

Habitat formed by the invasive macroalga Caulerpa filiformis (Suhr) Hering (Caulerpales, Chlorophyta) alters benthic macroinvertebrate assemblages in Peru - Silvia Aguilar; Pippa J. Moore; Roberto A. Uribe (Biological Invasions, 2022)

Global estimates of the extent and production of macroalgal forests - Carlos M. Duarte; Jean‐Pierre Gattuso; Kasper Hancke; Hege Gundersen; Karen Filbee‐Dexter; Morten F. Pedersen; Jack J. Middelburg; Michael T. Burrows; Kira A. Krumhansl; Thomas Wernberg; Pippa Moore; Albert Pessarrodona; et al. (Global Ecology and Biogeography, 2022)
Aim Macroalgal habitats are believed to be the most extensive and productive of all coastal vegetated ecosystems. In stark contrast to the growing attention on their contribution to carbon export and sequestration, understanding of their global extent and production is limited and these have remained poorly assessed for decades. Here we report a first data‐driven assessment of the global extent and production of macroalgal habitats based on modelled and observed distributions and net primary production (NPP) across habitat types. Location Global coastal ocean. Time period Contemporary. Major taxa studied Macroalgae. Methods Here we apply a comprehensive niche model to generate an improved global map of potential macroalgal distribution, constrained by incident light on the seafloor and substrate type. We compiled areal net primary production (NPP) rates across macroalgal habitats from the literature and combined this with our estimates of the global extent of these habitats to calculate global macroalgal NPP. Results We show that macroalgal forests are a major biome with a global area of 6.06–7.22 million km 2 , dominated by red algae, and NPP of 1.32 Pg C/year, dominated by brown algae. Main conclusions The global macroalgal biome is comparable, in area and NPP, to the Amazon forest, but is globally distributed as a thin strip around shorelines. Macroalgae are expanding in polar, subpolar and tropical areas, where their potential extent is also largest, likely increasing the overall contribution of algal forests to global carbon sequestration.

Examining the influence of regional‐scale variability in temperature and light availability on the depth distribution of subtidal kelp forests - Kathryn E. Smith; Pippa J. Moore; Nathan G. King; Dan A. Smale (Limnology and Oceanography, 2022)
Foundation species play a disproportionate role in maintaining biodiversity and ecosystem functioning. Improved understanding of how environmental factors influence the distribution and population structure of foundation species therefore contributes to management and conservation of entire ecosystems. We surveyed subtidal kelp forests within four regions of the U.K., distributed over 9° of latitude and a mean sea temperature gradient of ~ 2.5°C. Our aims were: (1) to examine relationships between light availability and the structure and depth distribution of Laminaria hyperborea populations and (2) to determine whether depth‐related patterns were consistent across regions with different temperature regimes. We recorded marked depth‐related shifts in structure with decreasing light levels strongly correlated with declines in kelp density, cover, plant biomass, standing biomass, plant length, and age. We also recorded an effect of latitude; populations at our two colder, northernmost regions exhibited greater wet weight and length and higher standing biomass than populations in the warmer southern regions when under similar or even reduced light conditions, indicating an interactive effect of latitude, most likely related to temperature variability. We show that shifts in kelp population structure along depth gradients are strongly driven by light availability, although regional variability in the strength and nature of these relationships may be promoted by other factors such as temperature. Maximum depth penetration, standing biomass, plant density, and plant weight are useful indicators of light availability and, over time, could be monitored to detect changes in the quality of the overlying water column.

Niche and neutral assembly mechanisms contribute to latitudinal diversity gradients in reef fishes - Nestor E. Bosch; Thomas Wernberg; Tim J. Langlois; Dan A. Smale; Pippa J. Moore; João N. Franco; Pierre Thiriet; Eric Feunteun; Cláudia Ribeiro; Pedro Neves; Rui Freitas; Karen Filbee‐Dexter; et al. (Journal of Biogeography, 2021)
Aim The influence of niche and neutral mechanisms on the assembly of ecological communities have long been debated. However, we still have a limited knowledge on their relative importance to explain patterns of diversity across latitudinal gradients (LDG). Here, we investigate the extent to which these ecological mechanisms contribute to the LDG of reef fishes. Location Eastern Atlantic Ocean. Taxon Reef‐associated ray‐finned fishes. Methods We combined abundance data across ~60° of latitude with functional trait data and phylogenetic trees. A null model approach was used to decouple the influence of taxonomic diversity (TD) on functional (FD) and phylogenetic (PD) diversity. Standardized effect sizes (SES FD and SES PD) were used to explore patterns of overdispersion, clustering and randomness. Information theoretic approaches were used to investigate the role of large‐ (temperature, geographic isolation, nitrate and net primary productivity) and local‐scale (human population and depth) drivers. We further assessed the role of demographic stochasticity and its interaction with species trophic identity and dispersal capacity. Results Taxonomic diversity peaked at ~15°–20°N, with a second mode of lower magnitude at ~45°N; a pattern that was predicted by temperature, geographic isolation and productivity. Tropical regions displayed a higher proportion of overdispersed assemblages, whilst clustering increased towards temperate regions. Phylogenetic and functional overdispersion were associated with warmer, productive and isolated regions. Demographic stochasticity also contributed largely to community assembly, independently of ecoregions, although variation was dependent on the trophic identity and body size of species. Main conclusions Niche‐based processes linking thermal and resource constraints to local coexistence mechanisms have contributed to the LDG in reef fishes. These processes do not act in isolation, stressing the importance of understanding interactions between deterministic and stochastic factors driving community structure in the face of rapid biodiversity change.

The intensity of kelp harvesting shapes the population structure of the foundation species Lessonia trabeculata along the Chilean coastline - Adam Gouraguine; Pippa Moore; Michael T. Burrows; Eliana Velasco; Luis Ariz; Luis Figueroa-Fábrega; Rodrigo Muñoz-Cordovez; Italo Fernandez-Cisternas; Dan Smale; Alejandro Pérez-Matus (Marine Biology, 2021)
Kelp are foundation species that support high levels of biodiversity and, either directly or indirectly provide a wide range of ecological goods and services to human society. In recent decades, due to the high demand for kelp-derived products such as alginate, commercial wild harvesting has increased, leading to declines of kelp biomass in some regions. Chile accounts for 40% of the global kelp harvest, with the subtidal kelp, Lessonia trabeculata being one of the main target species. Currently, however, there is a lack of information on how different degrees of harvesting intensity, governed by distinct management regimes and their enforcement influences L. trabeculata populations. Here we examined the effect different management regimes, characterised by distinct levels of exploitation of kelp and kelp-associated fauna, have on L. trabeculata density and morphology along ~ 1600 km of the Chilean coastline. The findings demonstrated that harvesting intensity likely influences both L. trabeculata density and morphology. Juvenile density of L. trabeculata was five times higher in the most harvesting-affected areas, while kelp morphology values, including holdfast diameter, number of stipes and total length, were always higher in the less-intensively harvested areas. Our study suggests that different degrees of protection can influence density and morphology of subtidal L. trabeculata populations, which in turn has important implications for the conservation of the kelp forest ecosystems and management of this important fishery.

Patterns and drivers of understory macroalgal assemblage structure within subtidal kelp forests - Dan A. Smale; Graham Epstein; Esther Hughes; Andrew O. M. Mogg; Pippa J. Moore (Biodiversity and Conservation, 2020)

Ecological performance differs between range centre and trailing edge populations of a cold-water kelp: implications for estimating net primary productivity - Nathan G. King; Pippa J. Moore; Albert Pessarrodona; Michael T. Burrows; Joanne Porter; Mathilde Bue; Dan A. Smale (Marine Biology, 2020)
Kelp forests are extensive, widely distributed and highly productive. However, despite their importance, reliable estimates of net primary productivity (NPP) are currently unknown for most species and regions. In particular, how performance and subsequent NPP change throughout a species range is lacking. Here, we attempted to resolve this by examining growth and performance of the boreal kelp, Laminaria digitata, from range centre and trailing edge regions in the United Kingdom. During the peak growth season (March/April), range-centre individuals were up to three times heavier and accumulated biomass twice as fast as their trailing-edge counterparts. This was not apparent during the reduced growth season (August/September), when populations within both regions had similar biomass profiles. In total, annual NPP estimates were considerably lower for trailing-edge (181 ± 34 g C m −2 year −1 ) compared to range-centre (344 ± 33 g C m −2 year −1 ) populations. Our first-order UK estimates of total standing stock and NPP for L. digitata suggest this species makes a significant contribution to coastal carbon cycling. Further work determining the ultimate fate of this organic matter is needed to understand the overall contribution of kelp populations to regional and global carbon cycles. Nevertheless, we highlight the need for large-scale sampling across multiple populations and latitudes to accurately evaluate kelp species’ contributions to coastal carbon cycling.

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Resistance, Extinction, and Everything in Between – The Diverse Responses of Seaweeds to Marine Heatwaves - Sandra C. Straub; Thomas Wernberg; Mads S. Thomsen; Pippa J. Moore; Michael T. Burrows; Ben P. Harvey; Dan A. Smale (Frontiers in Marine Science, 2019)

Projected Marine Heatwaves in the 21st Century and the Potential for Ecological Impact - Eric C. J. Oliver; Michael T. Burrows; Markus G. Donat; Alex Sen Gupta; Lisa V. Alexander; Sarah E. Perkins-Kirkpatrick; Jessica A. Benthuysen; Alistair J. Hobday; Neil J. Holbrook; Pippa J. Moore; Mads S. Thomsen; Thomas Wernberg; et al. (Frontiers in Marine Science, 2019)

Disentangling latitudinal diversity gradients in Taxonomic, Phylogenetic, and Functional diversity of Atlantic reef fishes - Nestor Bosch; Thomas Wernberg; Timothy Langlois; Dan Smale; Pippa Moore; João Franco; Pierre Thiriet; Eric Feunteun; Claudia Ribeiro; Pedro Neves; Rui Freitas; Karen Filbee-Dexter; et al. (Frontiers in Marine Science, 2019)

Carbon assimilation and transfer through kelp forests in the NE Atlantic is diminished under a warmer ocean climate - Albert Pessarrodona; Pippa J. Moore; Martin D. J. Sayer; Dan A. Smale (Global Change Biology, 2018)
Global climate change is affecting carbon cycling by driving changes in primary productivity and rates of carbon fixation, release and storage within Earth's vegetated systems. There is, however, limited understanding of how carbon flow between donor and recipient habitats will respond to climatic changes. Macroalgal‐dominated habitats, such as kelp forests, are gaining recognition as important carbon donors within coastal carbon cycles, yet rates of carbon assimilation and transfer through these habitats are poorly resolved. Here, we investigated the likely impacts of ocean warming on coastal carbon cycling by quantifying rates of carbon assimilation and transfer in Laminaria hyperborea kelp forests—one of the most extensive coastal vegetated habitat types in the NE Atlantic—along a latitudinal temperature gradient. Kelp forests within warm climatic regimes assimilated, on average, more than three times less carbon and donated less than half the amount of particulate carbon compared to those from cold regimes. These patterns were not related to variability in other environmental parameters. Across their wider geographical distribution, plants exhibited reduced sizes toward their warm‐water equatorward range edge, further suggesting that carbon flow is reduced under warmer climates. Overall, we estimated that Laminaria hyperborea forests stored ~11.49 Tg C in living biomass and released particulate carbon at a rate of ~5.71 Tg C year −1 . This estimated flow of carbon was markedly higher than reported values for most other marine and terrestrial vegetated habitat types in Europe. Together, our observations suggest that continued warming will diminish the amount of carbon that is assimilated and transported through temperate kelp forests in NE Atlantic, with potential consequences for the coastal carbon cycle. Our findings underline the need to consider climate‐driven changes in the capacity of ecosystems to fix and donate carbon when assessing the impacts of climate change on carbon cycling.

Categorizing and Naming Marine Heatwaves - Alistair Hobday; Eric Oliver; Alex Sen Gupta; Jessica Benthuysen; Michael Burrows; Markus Donat; Neil Holbrook; Pippa Moore; Mads Thomsen; Thomas Wernberg; Dan Smale (Oceanography, 2018)

Responses of Marine Organisms to Climate Change across Oceans - Elvira S. Poloczanska; Michael T. Burrows; Christopher J. Brown; Jorge García Molinos; Benjamin S. Halpern; Ove Hoegh-Guldberg; Carrie V. Kappel; Pippa J. Moore; Anthony J. Richardson; David S. Schoeman; William J. Sydeman (Frontiers in Marine Science, 2016)

Strengthening confidence in climate change impact science - Mary I. O'Connor; Johnna M. Holding; Carrie V. Kappel; Carlos M. Duarte; Keith Brander; Christopher J. Brown; John F. Bruno; Lauren Buckley; Michael T. Burrows; Benjamin S. Halpern; Wolfgang Kiessling; Pippa Moore; et al. (Global Ecology and Biogeography, 2015)
Aim To assess confidence in conclusions about climate‐driven biological change through time, and identify approaches for strengthening confidence scientific conclusions about ecological impacts of climate change. Location Global. Methods We outlined a framework for strengthening confidence in inferences drawn from biological climate impact studies through the systematic integration of prior expectations, long‐term data and quantitative statistical procedures. We then developed a numerical confidence index ( C index ) and used it to evaluate current practices in 208 studies of marine climate impacts comprising 1735 biological time series. Results Confidence scores for inferred climate impacts varied widely from 1 to 16 (very low to high confidence). Approximately 35% of analyses were not associated with clearly stated prior expectations and 65% of analyses did not test putative non‐climate drivers of biological change. Among the highest‐scoring studies, 91% tested prior expectations, 86% formulated expectations for alternative drivers but only 63% statistically tested them. Higher confidence scores observed in studies that did not detect a change or tracked multiple species suggest publication bias favouring impact studies that are consistent with climate change. The number of time series showing climate impacts was a poor predictor of average confidence scores for a given group, reinforcing that vote‐counting methodology is not appropriate for determining overall confidence in inferences. Main conclusions Climate impacts research is expected to attribute biological change to climate change with measurable confidence. Studies with long‐term, high‐resolution data, appropriate statistics and tests of alternative drivers earn higher C index scores, suggesting these should be given greater weight in impact assessments. Together with our proposed framework, the results of our C index analysis indicate how the science of detecting and attributing biological impacts to climate change can be strengthened through the use of evidence‐based prior expectations and thorough statistical analyses, even when data are limited, maximizing the impact of the diverse and growing climate change ecology literature.

Quantitative approaches in climate change ecology - Christopher J. Brown; David S. Schoeman; William J. Sydeman; Keith Brander; Lauren B. Buckley; Michael Burrows; Carlos M. Duarte; Pippa J. Moore; John M. Pandolfi; Elvira Poloczanska; William Venables; Anthony J. Richardson (Global Change Biology, 2011)
Contemporary impacts of anthropogenic climate change on ecosystems are increasingly being recognized. Documenting the extent of these impacts requires quantitative tools for analyses of ecological observations to distinguish climate impacts in noisy data and to understand interactions between climate variability and other drivers of change. To assist the development of reliable statistical approaches, we review the marine climate change literature and provide suggestions for quantitative approaches in climate change ecology. We compiled 267 peer‐reviewed articles that examined relationships between climate change and marine ecological variables. Of the articles with time series data ( n = 186), 75% used statistics to test for a dependency of ecological variables on climate variables. We identified several common weaknesses in statistical approaches, including marginalizing other important non‐climate drivers of change, ignoring temporal and spatial autocorrelation, averaging across spatial patterns and not reporting key metrics. We provide a list of issues that need to be addressed to make inferences more defensible, including the consideration of (i) data limitations and the comparability of data sets; (ii) alternative mechanisms for change; (iii) appropriate response variables; (iv) a suitable model for the process under study; (v) temporal autocorrelation; (vi) spatial autocorrelation and patterns; and (vii) the reporting of rates of change. While the focus of our review was marine studies, these suggestions are equally applicable to terrestrial studies. Consideration of these suggestions will help advance global knowledge of climate impacts and understanding of the processes driving ecological change.

Phenological changes in intertidal con‐specific gastropods in response to climate warming - PIPPA J. MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2011)
There is substantial evidence from terrestrial and freshwater systems of species responding to climate change through changes in their phenology. In the marine environment, however, there is less evidence. Using historic (1946–1949) and contemporary (2003–2007) data, collected from rocky shores of south‐west Britain, we investigated the affect of recent climate warming on the reproductive phenology of two con‐specific intertidal limpet grazers, with cool/boreal and warm/lusitanian centres of distribution. Reproductive development in the southern limpet, Patella depressa , has advanced, on average, 10.2 days per decade since the 1940s, with a longer reproductive season and more of the population reproductively active. The peak in the proportion of the population in advanced stages of gonad development was positively correlated with sea surface temperature (SST) in late spring/early summer, which has increased between the 1940s and 2000s. The advance in peak reproductive development of this species is double the average observed for terrestrial and freshwater systems and indicates, along with other studies, that marine species may be responding faster to climate warming. In contrast, the northern limpet, Patella vulgata , has experienced a delay in the timing of its reproductive development (on average 3.3 days per decade), as well as an increase in reproductive failure years and a reduction in the proportion of the population reaching advanced gonad stages. These results are the first to demonstrate a delay in the reproductive development of a cool‐temperate, winter spawner, towards cooler more favourable environmental conditions in response to climate warming. Such a delay in spawning will potentially lead to trophic miss‐matches, resulting in a rapid nonlinear decline of this species.

Predicting impacts of climate‐induced range expansion: an experimental framework and a test involving key grazers on temperate rocky shores - LOUISE B. FIRTH; TASMAN P. CROWE; PIPPA MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2009)
Climate change has strong potential to modify the structure and functioning of ecosystems, but experimental field studies into its effects are rare. On rocky shores, grazing limpets strongly affect ecosystem structure and their distribution in NW Europe is changing in response to climate change. Three limpet species co‐occur in SW Britain ( Patella vulgata, Patella ulyssiponensis and Patella depressa ) on open rock and in pools. Shores in Ireland are similar, but currently lack P. depressa . It is anticipated that P. depressa will expand its range into Ireland as the climate warms, but we currently lack an empirical basis to predict the consequences of this change. Recent studies show that increasing abundance of P. depressa on British shores has been accompanied by a decline of P. vulgata suggesting interspecific competition. In this study, a new experimental framework was used to examine the potential for P. depressa to affect P. vulgata on Irish shores. P. vulgata was experimentally transplanted into enclosures on open rock and in pools in both Ireland and Britain. In pools, treatments also included transplanted P. ulyssiponensis to mimic natural assemblages. Growth and mortality of P. vulgata were measured over 6 months with no differences between Ireland and Britain. In Britain, P. vulgata caged in pools with transplanted P. depressa and P. ulyssiponensis showed reduced growth, compared with when caged in pools with P. ulyssiponensis alone. There was no effect of P. depressa on the growth rate of P. vulgata on open rock. Results indicate that if the range of P. depressa extends into Ireland, it would reduce the growth of P. vulgata where it co‐occurs with P. ulyssiponensis in pools. The framework used here provides a field‐based approach that could be used to examine the impacts of climate‐induced range expansions on the structure and functioning of other ecosystems.

Spatial scales of variance in abundance of intertidal species: effects of region, dispersal mode, and trophic level - Michael T. Burrows; Robin Harvey; Linda Robb; Elvira S. Poloczanska; Nova Mieszkowska; Pippa Moore; Rebecca Leaper; Stephen J. Hawkins; Lisandro Benedetti-Cecchi (Ecology, 2009)
Determination of the pattern of variation in population abundance among spatial scales offers much insight into the potential regulating factors. Here we offer a method of quantifying spatial variance on a range of scales derived by sampling of irregularly spaced sites along complex coastlines. We use it to determine whether the nature of spatial variance depends on the trophic level or the mode of dispersal of the species involved and the role of the complexity of the underlying habitat. A least‐cost distance model was used to determine distances by sea between all pairs of sites. Ordination of this distance matrix using multidimensional scaling allowed estimation of variance components with hierarchical ANOVA at nested spatial scales using spatial windows. By repeatedly moving these spatial windows and using a second set of spatial scales, average variance scale functions were derived for 50+ species in the UK rocky intertidal. Variance spectra for most species were well described by the inverse power law (1/ f β ) for noise spectra, with values for the exponent ranging from 0 to 1.1. At higher trophic levels (herbivores and carnivores), those species with planktonic dispersal had significantly higher β values, indicating greater large‐ than small‐scale variability, as did those on simpler coastlines (southwestern England and Wales vs. western Scotland). Average abundance and proportional incidence of species had the strongest influence on β values, with those of intermediate abundance and incidence having much greater large‐scale variance (β ≈ 0.5) than rare or ubiquitous species (β ≈ 0).

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.